Implikasi Kebijakan Fiskal Terhadap Distribusi Pendapatan Dan Kesejahteraan Masyarakat - Nurmaini, Nurmaini; Zakir, Muhammad; Assyifa, Zubaidah (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This research aims to analyze the implications of fiscal policy on income distribution and social welfare. Fiscal policy, which includes tax instruments and government spending, has a strategic role in creating economic equality and reducing social inequality. This study uses a qualitative approach with descriptive-analytical methods, based on secondary data obtained from various sources, such as government reports, academic journals and economic publications. The research results show that appropriate fiscal policies, such as a progressive tax system and effective allocation of social spending, can increase income distribution more evenly and promote social welfare. However, less than optimal policy implementation has the potential to worsen economic inequality. Therefore, continuous evaluation and policy design is needed based on the principles of justice and efficiency to achieve inclusive economic growth